Improving Students Language Skills Through New Integrated Approaches in Modern Language Teaching (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the effectiveness of new integrated approaches in enhancing students’ language skills within modern language teaching. As traditional, isolated-skill instruction becomes increasingly insufficient for meeting contemporary educational demands, integrated approaches combining listening, speaking, reading, and writing offer a more holistic and communicative framework. The study examines how task-based learning, project-based activities, multimedia resources, and technology-enhanced instruction contribute to deeper language acquisition and improved learner autonomy. Attention is given to the pedagogical principles that support integration, including meaningful input, collaborative interaction, contextualized practice, and reflective learning. The article also analyzes classroom implications, highlighting the role of authentic materials, multimodal tasks, and digital platforms in fostering engagement and facilitating real-world language use. Findings indicate that integrated approaches not only enhance linguistic competence but also develop critical thinking, cultural awareness, and learner motivation. The study concludes that adopting integrated methodologies is essential for modern language classrooms seeking to prepare students for dynamic communication in a globalized world.